Sustainable Business Development Models for Regional Airports - Anatoli Beifert; Gunnar Prause; Laima Gerlitz (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
As it was outlined in the EU Competition Policy Brief on the new state aid rules for a competitive aviation industry issued by the EU Competition Directorate-General in February 2014, the regulation for the financial public subsidies of any art on the EU national or regional level for the regional airports will be considerably striker. The strategic aims of these new regulations, among other things, are to motivate and encourage the Member States (here: regional airports) to implement more efficient market stimulation measures, make airports work on cost efficient and profit-able basis and establish transition periods for regional airports. In practice it means that public subsidies may be granted only to those regional airports that proved to have a sustainable and realistic business model that shall clearly demonstrate the durable financial stability. The authors took part in two air transportation initiatives in the Baltic Sea regions (BSR) and were lead partner in the EU Project Baltic.AirCargo.Net, which deployed a number of empirical measures in regional airports in the BSR. The paper will present and discuss success factors of sustainable business development models for the regional airports in the Baltic Sea Region based on cases studied during the project lifetime.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Business Models; Regional Airports; Sustainability